(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
It is known that until the mid-70s of the XX century, the problems of linguistic conceptualization, as well as the linguistic realization of feelings, did not attract the attention of linguists. But due to the fact that at the heart of the new linguistic paradigm is a person and his language, the psychology of the language carrier, linguists could not bypass the sphere of emotions. The study of the linguistic aspects of emotions shows, on the one hand, the relevance of the language of emotions for communicative communication between people, and on the other hand, the accumulation of many empirical materials related to their study in World linguistics. Although several studies on the study of emotional concepts in World linguistics have been carried out, this concept has not been studied in Uzbek linguistics in a monographic aspect together with the problems of the landscape of a separate emotional-linguisticuniverse. Despite the fact that today the study of the language of emotions has begun in Uzbek linguistics, the concept of “emotional concept” itself does not yet have enough definition. Therefore, the article discusses the introduction of the concept of emotion into scientific circulation, its meaning, scientific interpretation and the relevance of the study of this concept.